The Internet in Cyprus 2012, Final Report - Milioni, Dimitra L.; Stylianou, Stelios (Department of Communication and Internet Studies, Cyprus University of! Technology, 2013)
The third wave of the World Internet Project survey in Cyprus was conducted in the fall of 2012 in both the Greek\Cypriot and the Turkish\Cypriot communities.The data were collected by two telephone surveys,one in the Greek\Cypriot community with a probability sample of 1000 persons aged 15 or over and one in the Turkish\Cypriot community with a probability sample of 1007 persons aged 15 or over.In the first part of the report,we present trends in internet use in the Greek\Cypriot community from 2008 to 2012.In the second part,we present a comparison between the Greek\Cypriot and the Turkish\Cypriot communities in 2012.
Keywords: Τelephone surveys; Greek\Cypriot community; Turkish\Cypriot community; Trends in internet